PEDIATRIC ORTHOPEDIC RADIOGRAPH REDUCTION: A QUALITY IMPROVEMENT INITIATIVE. Issue 4 (28th April 2020) - Lander, Sarah; Michels, Julie; Brayer, Anne; Obudzinski, Sarah; D'amore, Taylor; Chess, Mitchel; Wakeman, Derek; Cook, P. Christopher; Sanders, James
Background: Children are more vulnerable to ionizing radiation which increases health risks later in life including cancer. An interdepartmental team developed an algorithm to guide providers ordering extremity radiographs in pediatric patients with musculoskeletal (MSK) injuries. Purpose: Reduce unnecessary pediatric radiation/extremity radiographs through development and implementation of an interdepartmental designed algorithm. Determine utility, safety, and efficacy of the algorithm through retrospective and prospective analysis. Methods: Our study was performed at an academic pediatric trauma center. An interdepartmental committee including pediatric orthopedic surgery, emergency medicine, trauma, and radiology providers created a MSK injury imaging algorithm (Figure 1). We retrospectively validated the algorithm for efficacy and safety through chart review of pediatric patients seen in the ED with MSK extremity injury, identified through CPT code, from 6/24/2016 through 8/31/2016. We determined the number of extra radiographs per patient and identified if injuries would be missed utilizing our protocol. After retrospective validation, guideline implementation was undertaken through multidisciplinary education. The imaging guideline was prospectively implemented in the pediatric ED from 6/24/2018 through 8/31/2018. We continued to prospectively evaluate through selecting one week every month over the following eight months to determine sustainability of the implemented algorithm. Results: Our interdepartmental team in 2016 developed a pediatric MSK radiograph protocol (Figure 1). A retrospective chart and radiograph review of 295 pediatric patients between 6/24/2016 through 8/31/2016 was analyzed correlating physical examination to appropriate radiographs. Utilizing the protocol, the review revealed an average of 2.75 extra radiographs per patient. No injuries were missed. Providers including orthopedic and emergency medicine attendings, mid-levels, and residents were educated through meetings, emails, and having the protocol posted and easily accessible. Our protocol was implemented 6/24/18 and underwent prospective enrollment and review through 8/31/18 which revealed a reduction to 0.72 radiographs per patient (P-value <0.001) (Figure 2). Eight month follow up revealed a sustainable reduction in extra radiographs per patient (Figure 3). Conclusion: Reduction of unnecessary radiation to pediatric patients with MSK extremity injuries was accomplished through development and implementation of a safe and effective imaging algorithm. The multidisciplinary approach combined with widespread education of pediatric providers improved buy-in driving a sustainable system improvement. : Figure 1. Pediatric Extremity Injury Algorithm Figure 2. Average number of radiographs per pediatric patient not indicated by imaging algorithms before and after protocol implementation. (P<0.001) Figure 3. Eight month follow up of average number of extra radiographs per patient